The zinc finger protein560(ZNF560) functions as a novel oncogenic gene in osteosarcoma - Xiong Dong; Guanhua Xu; Hongxiang Hong; Jinlong Zhang; Zhiming Cui; ZiLiang Yu (Scientific Reports)
Abstract Background: Abnormal expression of Zinc finger (ZNF) genes is commonly observed in osteosarcoma (OS), the most prevalent malignant bone tumor in children and teenagers. This project focused on the role of ZNF560 in the progress of OS. Methods: The published datasets including TCGA-SARC and GSE99671 was utilized to screen out the abnormal expression of ZNF560 and associated gene patterns in sarcoma and OS tissues. Prognosis value of ZNF560 was identified in TCGA-SARC and OS cohorts. In order to manipulate ZNF560 expression in HOS and MG63 osteosarcoma (OS) cells, genetic strategies such as shRNA constructs were utilized. The expression patterns of ZNF560 were analyzed through techniques such as immunohistochemistry, Western blotting, and qRT-PCR. Results: By analyzing data from both the GEO and the Cancer Genome Atlas (TCGA) databases, increased expression of ZNF560 in OS tissues was verified, which was significantly associated with poorer outcomes in osteosarcoma patients both in TCGA-SARC and our own OS cohorts. Additionally, downregulation of ZNF560 resulted in decreased cell viability, fewer colonies, and induced apoptosis of osteosarcoma cells. Moreover, ZNF560 was found to be essential for migration of human osteosarcoma HOS and MG63 cells. Conclusion: Collectively, these findings suggest that ZNF560 has the potential to serve as a predictive biomarker for osteosarcoma.